2003
DOI: 10.1063/1.1594717
|View full text |Cite
|
Sign up to set email alerts
|

Collision dynamics of large water clusters on graphite

Abstract: Articles you may be interested inA molecular-beam study of the collision dynamics of methane and ethane upon a graphitic monolayer on Pt (111) The emission of neutral cluster fragments during collisions of large water clusters with graphite surfaces has been investigated using molecular beam techniques. Water clusters with an average size of up to 1.4•10 4 molecules per cluster collide with the surface with a velocity of 1380 ms Ϫ1 . Angular distributions for emitted large fragments are shifted towards the tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The calculations performed in the present study are of the same type as the ones presented in refs , , and 8, and for a detailed description we refer to these papers. The initial conditions were chosen to resemble the conditions during cluster beam experiments, where large water clusters impinged on a graphite surface at surface temperatures T surface ≤ 1400 K. In the experiments, the average incident cluster size was ≤ 14 000 monomers/cluster, but the distribution extended up to n > 20 000. We have simulated collisions between (H 2 O) n and graphite, where n has been set to 4094, 12 516, and 25 159 to mimic different parts of the incident size distribution in the experiments.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculations performed in the present study are of the same type as the ones presented in refs , , and 8, and for a detailed description we refer to these papers. The initial conditions were chosen to resemble the conditions during cluster beam experiments, where large water clusters impinged on a graphite surface at surface temperatures T surface ≤ 1400 K. In the experiments, the average incident cluster size was ≤ 14 000 monomers/cluster, but the distribution extended up to n > 20 000. We have simulated collisions between (H 2 O) n and graphite, where n has been set to 4094, 12 516, and 25 159 to mimic different parts of the incident size distribution in the experiments.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Clusters this large typically have diameters of a few nanometers and approach the macroscopic size range. Cluster beam experiments and MD simulations have shown that when nanometer-sized water clusters collide with graphite, large fragments may leave the surface by means of two different mechanisms: evaporation-mediated emission and direct scattering. The evaporation-mediated mechanism is in operation at surface temperatures above 700 K and can be divided into three stages: (i) cluster deformation on surface impact, (ii) cluster heating by the hot surface, and (iii) cluster emission driven by evaporation of monomers and small fragments.…”
Section: Introductionmentioning
confidence: 99%
“…The MD simulations of impinging metal clusters, such as molybdenum, aluminum, and copper, were performed to investigate deposition, deformation, and fragmentation on the surface of the same metal species , and the rigid surface . Tomsic et al reported both experiments and MD simulations of impinging ice clusters on hot surfaces. The evaporation and bouncing of the ice clusters were studied at surface temperatures between 300 and 1400 K. They found two types of bounce-back behaviors: evaporation and elastic bouncing. When the surface temperature was 1400 K, the impinging ice clusters, whose initial temperature was 180 K, were heated by the hot surface and bounced back due to evaporation of monomers and small fragments of water molecules on the surface .…”
Section: Introductionmentioning
confidence: 99%
“…The issue of droplet–wall collisions is of interest also in other fields of research, ranging from controlled cluster deposition over surface cleaning by cluster impact to cluster-impact chemistry . The fragmentation of pure droplets (without embedded macromolecules) has been studied previously for clusters composed of van der Waals-bonded atoms and molecules , and, in particular, also for water. The collision of a protein-loaded droplet with a wall has only rarely been studied before …”
Section: Introductionmentioning
confidence: 99%